Accessory parotid gland: its surgical importance - Ashutosh Mangalgiri; Devendra Mahore (International Journal of Medical Research and Review, 2016)
Introduction: Accessory parotid gland is separated normal tissue from the main parotid gland, lying over the parotid duct. Accessory parotid gland is more prone for parotid tumors than main parotid gland. The accessory parotid is the site of congenital and acquired lesions. It usually presents as mid cheek swelling. Mid cheek incision may damage branches of facial nerve.Material & Method: Forty parotid glands were dissected from 20 cadavers during a period of 2 years from 2014 to 2016. Dissections were carried out at Chirayu Medical College & Hospital, Bhopal.Result: Out of 40 parotid glands dissected, accessory parotid glands were observed in 3 cases on right side. Incidence was found to be 7.5% for the present study. Accessory parotid gland was observed on right side lying on parotid duct detached from the main mass of the parotid gland. In case 2, accessory parotid was observed lying on parotid duct and here gland has two different ducts draining separately.Conclusion: Accessory parotid gland is the commonest site for pleomorphic adenoma. It may present as a slowly progressive mid cheek mass. They are more in accessory parotid than main mass of parotid gland. The accessory parotid not often mentioned variant is separate from main parotid gland should be addressed properly to ensure complete removal of disease. This is very important in malignancy for surgical clearance.